The Best of Once Upon a Christmas Cheery in the Lab of Shakhashiri - Shakhashiri, Bassam Z. (2011)
This is a compilation of segments from the series of annual Christmas lectures given by Bassam Z. Shakhashiri, a Lebanese chemistry educator who spent most of his career at the University of Wisconsin-Madison. All segments in this compilation are from 2004-2010. Most of these segments involve guests: local high school students, University of Wisconsin professors, and community members, including oboe professor Mark Fink, bassoon professor Mark Vallon, voice and acting professor Clare Arena Haden, opera singer Allan Naplan, and University of Wisconsin Marching Band Director Mike Leckrone. All of the guests who assist in the chemistry experiments also play a musical instrument or sing, and demonstrate the connection between science and art.
Keywords: Chemistry--Experiments; Christmas; Educational films; Lectures; Science--Study and teaching; Liquid nitrogen; University of Wisconsin--Madison; Music and science